Program Gerakan Masyarakat Cerdas Menggunakan Obat Di Kota Medan Tahun 2020 - Fitriani Pramita Gurning; Marlina Yusnita Nasution; Lilis Ananda; Fenny Dwi Arini (Jurnal Kesehatan, 2021)
The Smart Community Movement Using Drugs (GeMa CerMat), a Ministry of Health program that involves cross-sectoral and community components. GeMa CerMat activities are aimed at increasing knowledge and skills, as well as changing people's behavior in choosing, obtaining, using, storing and disposing of medicines properly. Riskesdas 2013 data shows that 35.2% of households store medicines for self-medication. Referring to 35.2% of households who store drugs, 35.7% of them store hard drugs, and 27.8% of them store antibiotics and 86.1% of antibiotics are obtained without a prescription. This situation shows that self-medication has not been implemented properly. The research objective was to analyze the GeMa CerMat program in Medan City. The research method used in this research is descriptive research using a qualitative approach. The results of the study show that the Medan City Health Office data for the achievement of indicators in the Medan City area in 2019 is 60.6% with a target of 60%, in the previous year the indicator achievement was 5.13% with a target of 55% of the achievement of the indicators for the CerMat GeMa Program in the City area. Medan in 2020 the achievement target of 45% for Medan City was not achieved according to the target due to the Covid-19 pandemic so that the GeMa CerMat program was not implemented.